2009
DOI: 10.1007/s11661-009-0115-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing Parameters on Microstructure and Mechanical Properties of an Al-Al11Ce3-Al2O3 In-Situ Composite Produced by Friction Stir Processing

Abstract: Friction stir processing (FSP) was applied to produce aluminum-based in-situ composites from powder mixtures of Al-5 mol pct CeO 2 . A billet of powder mixtures was prepared using the conventional pressing and sintering route. The sintered billet was then subjected to multiple passages of FSP. This technique has combined the hot-working nature of FSP and the exothermic reaction between Al and CeO 2 . The reinforcing phases were identified as Al 11 Ce 3 and d * -Al 2 O 3 . The Al 2 O 3 particles with an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Formation of nanosized reaction products with coherent or semicoherent interfaces can enhance mechanical properties. Various hybrid aluminium matrix nanocomposites were fabricated by FSP using Al–CeO 2 (Chen et al ., ), Al–TiO 2 (Khodabakhshi et al ., , Zhang et al ., , Zhang et al ., ), Al–CuO (You et al ., ) and Al–Fe 2 O 3 (Azimi‐Roeen et al ., ) systems, where in situ formation of Al 2 O 3 particles occurred by reactive mechanisms. However, because FSP interaction time is limited, the reaction may not be completed.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of nanosized reaction products with coherent or semicoherent interfaces can enhance mechanical properties. Various hybrid aluminium matrix nanocomposites were fabricated by FSP using Al–CeO 2 (Chen et al ., ), Al–TiO 2 (Khodabakhshi et al ., , Zhang et al ., , Zhang et al ., ), Al–CuO (You et al ., ) and Al–Fe 2 O 3 (Azimi‐Roeen et al ., ) systems, where in situ formation of Al 2 O 3 particles occurred by reactive mechanisms. However, because FSP interaction time is limited, the reaction may not be completed.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir processing, which is basically considered to be an advanced process for grain refinement technique, has become very popular in fabricating surface composites and nanocomposite layers [11][12][13]. But a completely uniform distribution cannot be achieved and it is recommended that multiple passes are needed to improve the distribution of nanoparticles in the metal matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches [7,8] have shown that aluminum matrix composites reinforced by in situ formed Al 2 O 3 nanoparticles can be fabricated by FSP in Al-CeO 2 [7] and Al-TiO 2 [8] systems. These composite exhibited enhanced strength due to the fine dispersion of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%